Implementasi Battery Management System Pada PLTS Hibrida Skala Kecil - Binar Surya Gumilang; Mohammad Noor Hidayat; Rohmanita Duanaputri; Salman Alfarisi (Politeknik Negeri Malang, 2025)
This study investigated the implementation of a Battery Management System (BMS) as a protective and performance-enhancing component in a small-scale hybrid solar power plant storage system rated at 10 × 100 Wp. Battery degradation, voltage imbalance, and excessive discharge currents are persistent challenges in off-grid and hybrid photovoltaic systems, particularly in rural electrification applications. The purpose of this research was to evaluate the effectiveness of an active cell balancing–based BMS in improving battery voltage stability, regulating discharge current, and extending battery life cycles.The research employed an experimental method by comparing system performance before and after BMS installation under identical charging and discharging conditions. Experimental results showed that prior to BMS installation, charging voltages among four VRLA batteries were unbalanced, ranging from 13.70 V to 13.80 V, and discharge currents reached up to 50.3 A. After BMS implementation, charging voltages became uniform at approximately 13.44 V, while discharge currents were limited to a maximum of 29.9 A. Furthermore, the SOC threshold was regulated from 100% to 90%, and discharge duration increased from 1.5 hours to 2 hours. Based on battery datasheet analysis, the estimated battery life cycle increased from a maximum of 372 cycles to 572 cycles. These findings indicate that the integration of a BMS with active cell balancing significantly enhances operational stability, thermal safety, and battery longevity. The results imply that BMS adoption is essential for improving reliability and sustainability of small-scale hybrid solar energy systems.